2023
DOI: 10.36923/ijsser.v5i2.177
|View full text |Cite
|
Sign up to set email alerts
|

Does work stress & workplace incivility influence Employee Turnover Intentions? Mediating Role of Work-family Conflict

Abstract: Purpose: The purpose of this study was to assess the impact of work stress and workplace incivility on turnover intention and work-family conflict. As well as the role of work-family conflict in mediating the relationship between work stress, workplace incivility, and turnover intention. Design/methodology/approach: The data was collected by distributing 573 questionnaires to nurses working in the healthcare sector in Punjab, Pakistan. The SPSS (23) statistical package was used to analyze the data, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…(Nauman, Fatima & Haq, 2018). Similarly, abusive supervision affects turnover through the damaging mental and emotional state reported among healthcare workers by Mehmood, Aziz, and Husin (2023).…”
Section: Introductionmentioning
confidence: 99%
“…(Nauman, Fatima & Haq, 2018). Similarly, abusive supervision affects turnover through the damaging mental and emotional state reported among healthcare workers by Mehmood, Aziz, and Husin (2023).…”
Section: Introductionmentioning
confidence: 99%
“…In line with findings from (Poku et al, 2022) and (Wan et al, 2018) which results in that the work environment has a significant effect on turnover intention. As well as the study by (Mehmood et al, 2023) and (Bajaba et al, 2022) which states that WFC has a significant effect on turnover intention.…”
Section: Introductionmentioning
confidence: 72%
“…In addition, this study observed that burnout, to some extent, mediates the relationship between work-family conflict and turnover intention, and the mediating effect is significant. Although there had been studies exploring the relationship between turnover intention, burnout, and workfamily conflict, there was limited research literature on the three factors mentioned above among primary medical staff, and there was even more limited research on the role of burnout in the relationship between work-family conflict and turnover intention (41)(42)(43)(44)(45). Therefore, attention needs to be paid to work-family conflict, burnout, and turnover intention among primary medical staff (46-48).…”
Section: Discussionmentioning
confidence: 99%